Digital Technology Usage Influence on the Effectiveness of the Construction Implementation Team - Pinondang Simanjuntak (International Journal of Social Service and Research (IJSSR), 2023)
The construction project implementation team generally consists of clients, project managers, financiers, legal consultants, design leaders (architects or structural engineers), other specialized consultants, main contractors, subcontractors, cost consultants and suppliers, who must work together effectively to realize project objectives. Under these conditions and with current technological developments, the role of using digital technology will become an important part of the effectiveness of the project implementation team. This study aims to determine the positive influence of digital technology (digitalization) on the effectiveness of the project implementation team. This research is a survey research, involving 200 company respondents, members of the construction industry professional association in Jakarta. Multiple regression was used to analyze the data. The results of the study show that digital technology (digitalization) has a significantly positive effect on the effectiveness of the project implementation team.